A biodiesel production process catalyzed by the leaching of alkaline metal earths in methanol: from a model oil to microalgae lipids. Issue 5 (1st November 2016) - Veillette, Marc; Giroir‐Fendler, Anne; Faucheux, Nathalie; Heitz, Michèle
Abstract: BACKGROUND: A response surface methodology was used to study the reaction mechanism of strontium oxide (SrO) as a catalyst for a biodiesel production process using a model oil (composed of fatty acid methyl esters (FAME), free fatty acids (FFAs) and triglycerides). The influence of several factors (initial FAME content (0–30 wt%), initial FFAs content (oleic acid 0.20–2.7 wt%), temperature (40–60 °C), methanol to model oil ratio (11–43 wt%), catalyst to model oil ratio (0.5–2.5 wt%) and reaction time (5–30 min)) on the FAME yield, the FAME content, the pH of polar phase and the biodiesel alkalinity was studied. SrO was also compared with potassium hydroxide (KOH) for the conversion of Scenedesmus Obliquus microalgae esterified lipids after a first step of FFAs esterification with sulfuric acid into biodiesel with the following conditions: temperature: 60 °C; reaction time: 22.2 min; catalyst to microalgae ratio: 2.48 wt%; methanol to microalgae lipid ratio: 31.4 wt%. RESULTS: With those operating conditions, KOH was able to reach a slightly higher FAME yield (32.6% g FAME g −1 lipid) than SrO (29.0% g FAME g −1 lipid). Moreover, the results showed a strong relationship between the pH of the polar phase (glycerol–methanol–water) and the FAME yield, which indicates that the reaction using alkaline metal earths is mostly catalyzed by a homogeneous reaction. CONCLUSION: The fact that alkaline metal earths act as homogeneous catalysts make them less suitable for biodiesel production, because they are not inducing neutral pH, and they increase the risk of corrosion. © 2016 Society of Chemical Industry